In vivo CAMPATH-1H prevents GvHD following nonmyeloablative stem-cell transplantation. - Kottaridis, P; Milligan, D; Chopra, R; Chakraverty, R; Chakrabarti, S; Robinson, S; Peggs, K; Verfuerth, S; Pettengell, R; Marsh, J; Schey, S; Mahendra, P; et al. (2001)
BACKGROUND: We have investigated a novel nonmyeloablative conditioning regimen in 44 patients with hematological malignancies. The median patient age was 41 years. Many of the patients had high-risk features, including 19 patients with a previous failed transplant. METHODS: Recipient conditioning consisted of CAMPATH-1H 20 mg/day on Days -8 to -4, fludarabine 30 mg/m(2) on Days -7 to -3 and melphalan 140 mg/m(2) on Day -2. Thirty-six recipients received unmanipulated G-CSF mobilized PBSC from HLA identical siblings and eight received unmanipulated BM from MUD. GvHD prophylaxis was with CYA alone for 38 patients and CYA plus MTX for six sibling recipients. RESULTS: Forty-two of the 43 evaluable patients had sustained engraftment. Results of chimerism analysis using microsatellite PCR indicate that 18 of 31 patients studied were full donor chimeras, while the other patients were mixed chimeras in one or more lineages. At a median follow-up of 9 months (range, 3-29 months) 33 patients remain alive in CR, or with no evidence of disease progression. Seven patients relapsed or progressed post-transplant and four of them subsequently died. Four patients died from regimen-related complications. There were no cases of Grades III-IV acute GvHD. Only two patients developed Grade II acute GvHD and only one had chronic GvHD. The estimated probability of non-relapse mortality at 1 year was 11%.Results: Although longer follow-up is needed to establish the long-term remission rates, this study demonstrates that this nonmyeloablative preparative regimen is associated with durable engraftment, minimal toxicity and low incidence of GvHD.